Empowerment Strategy for the Coffee Product Innovation in Wates Village, Jenangan District, Ponorogo Regency - Della Prisca Devi Astrayasana; Dita Febra Rusaliana; Ersa Rosyana; Putri Amulia; Salma Dinda Kharisma; Muhammad Azzam Muttaqin (Society : Jurnal Pengabdian Masyarakat, 2023)
Basirsa type coffee which is a typical coffee of Wates Village, Jenangan District, has great potential to be developed into processed products that have more high economic value. Therefore, this study aims to determine the appropriate development strategy for processed Basirsa coffee products to be applied in Wates Village, Jenangan District. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation studies. The results of the study indicate that there are several factors that need to be considered in the development of processed Basirsa coffee products, namely the selection of quality raw materials, the selection of the right processing technology, attractive and environmentally friendly product packaging, as well as an effective and efficient marketing strategy. In developing processed Basirsa coffee products, good cooperation is needed between coffee farmers, coffee processors and other related parties, as well as support from the local government.